2015
DOI: 10.1016/j.jveb.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anesthetics on carotenoid pigmentation and behavior in Arctic char (Salvelinus alpinus)

Abstract: Status of individual animals is often shown in pigmentation. For instance, stress responsiveness is associated with melanin-based pigmentation in vertebrates in general. This pattern is evident in Atlantic salmon (Salmo salar) and rainbow trout (Onchorhynchus mykiss) with melanin-based spots indicating stress coping style. Arctic charr (Salvelinus alpinus) differ from other salmonids in pigmentation but have an association between carotenoid-based pigmentation and stress coping style. These pigmentation differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
(46 reference statements)
2
11
1
Order By: Relevance
“…Further this trend was to some extent evident in spots on the left side on day 9 but not on day 8. This is in line with the report that anaesthesia induced carotenoid spots in Arctic charr (Backström et al 2015b), as well as the reported stress-inducing effect of the anaesthetic MS-222 in teleost fish (Zahl et al 2010;Readman et al 2013). Thus the anaesthetic treatment before photographing could arguably be the more stressful handling.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Further this trend was to some extent evident in spots on the left side on day 9 but not on day 8. This is in line with the report that anaesthesia induced carotenoid spots in Arctic charr (Backström et al 2015b), as well as the reported stress-inducing effect of the anaesthetic MS-222 in teleost fish (Zahl et al 2010;Readman et al 2013). Thus the anaesthetic treatment before photographing could arguably be the more stressful handling.…”
Section: Discussionsupporting
confidence: 89%
“…Immediately after photographing, fish were anaesthetized with Tricaine methane sulfonate (MS-222, 0.15 g/L), weighed and measured. The fish were not anaesthetized prior to photographing based upon the apparent spot inducing effects by anaesthetics in Arctic charr (Backström et al 2015b). Isolation of individual fish was created by separating experimental aquaria (170 L, 95 x 41 x 44 cm) into four equally-sized 42.5 L compartments using removable dark PVC walls.…”
Section: Experiments Setupmentioning
confidence: 99%
See 3 more Smart Citations